A UK‐wide survey looking at teaching and trainee confidence in teledermatology: a vital gap in a COVID‐19‐induced era of rapid digital transformation?. (1st October 2020) - Lowe, A.; Pararajasingam, A.; Goodwin, R.
Summary: Teledermatology has had an explosive impact on the provision of dermatology services in recent times, and even more so with the unprecedented situation created by the COVID‐19 pandemic. Although teledermatology is not presently a feature of the Joint Royal Colleges of Physicians Training Board (JRCPTB) curriculum for dermatology training, this is due to change imminently. Specialty trainees need training in this area to be able to confidently and competently meet the demands of the changing face of dermatology services. We surveyed dermatology registrars in training across the UK, prior to the outbreak of COVID‐19, to ascertain the teledermatology teaching available and trainee confidence in this area. Our survey found that only 15% of respondents felt slightly confident in their ability to deal with teledermatology referrals and almost all (96%) felt more teaching was needed.